How are Art Librarians Using Information Literacy Instruction to Support Art Studio Students? - Huot, Ashley (Pathfinder: A Canadian Journal for Information Science Students and Early Career Professionals, 2023)
This literature review examines how art librarians are using information literacy instruction (ILI) to support student research and information needs in art studio practices. The review contextualizes the topic, and identifies current strategies, gaps, and considerations for areas of future growth for a student population that is often underserved by libraries. The review thematically considers the impact of standards and frameworks on ILI in the arts and current strategies in art information literacy instruction. Findings include a need for growth and literature on the subject, disconnects between literature from the field of art, art history, and librarianship, and that recent competency documents have resulted in significant and beneficial pedagogical shifts, concluding that there are many promising future areas of growth and innovative potential for ILI in studio art contexts.